Natural Language Processing with Deep Neural Networks - Tolias, Kyriakos (Department of Electrical Engineering, Computer Engineering and Informatics, 2020)
Since the very first days of the Computer Era, machines provided us the ability to collect and store vast amount of information. It, soon, became obvious that harvesting information was an entirely different task, much more complicated and demanding. Many solutions developed to make it possible for humans to communicate with computers, aiming data mining. Databases, query languages and search engines were for decades the most prevalent solution. At first, special skills were required such as query language knowledge or search engine’s syntax to be able to perform advanced tasks. In order to be adopted by users, search should be easy and human friendly. Nowadays, search engines are using simple language syntax and have made significant progress towards natural language path. Still, search engines fall sort on combining information from different parts producing a synthetic answer. Computers are actually computational machines, therefore are excellent at manipulating syntax and calculating words’ frequency but are weak in recognizing concepts behind the words. A traditional search engine, is not able to draw conclusions or realize the context of a dialogue. Machine Learning has been proven strong in dealing with such concepts. One of the most challenging fields of machine learning is the Natural Language Processing (NLP), especially its component Natural Language Understanding (NLU). The crest of NLP are the question-answering and summarization tasks, in sense that strong cognitive ability is required in order the conceptual context to be extracted. Supervised learning of deep neural networks, is currently the best available tool for these tasks. Despite the rapid advances in the field of Machine Learning, their performance remains poor when dealing with hard NLU and NLP tasks, such as abstractive summarisation and question answering. This dissertation aims to offer substantive and measurable progress in both these areas, by ameliorating a key problem of modern machine learning techniques: The need for dense and large data corpora for effective model training. This is an especially hard task in the context of such applications. To this end, we leverage arguments from the field of Bayesian inference. This allows for better dealing with the modelling uncertainty, which is the direct outcome of data sparsity, and results in poor modelling/generalisation performance. Our approaches are founded upon solid and elaborate statistical inference arguments, and are evaluated using challenging popular benchmarks. As we show, they offer tangible performance advantages over the state-of-the-art.
Keywords: Deep Learning; Machine Learning; Bayesian Inference; Variational Bayes; Natural Language Processing